THE INFLUENCE OF KNOWLEDGE AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT BKKBN REPRESENTATIVES IN RIAU PROVINCE - Muhammad Syahril; Ikhwani Ratna (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
The purpose of this study was to analyze the effect of knowledge and work experience on employee performance in the BKKBN Riau Province. Knowledge and work experience are important factors that can affect employee performance in carrying out their duties and responsibilities. This research uses a quantitative method with a survey approach, which involves collecting data through questionnaires distributed to employees at the BKKBN Riau Province. Data analysis was conducted using multiple regression statistical techniques to identify the influence of each independent variable, namely knowledge and work experience, on the dependent variable, namely employee performance. The result of this study is that there is a simultaneous significant influence between knowledge and work experience on employee performance in the BKKBN Riau Province. The results of the study are expected to provide useful insights for the management of BKKBN Riau Province in formulating effective human resource development strategies to improve employee performance. In addition, this research is also expected to contribute to the literature on factors that affect employee performance in the government sector.